Laser ignition of elastomer-modified cast double-base (EMCDB) propellant using a diode laser - Herreros, Dulcie N.; Fang, Xiao (Elsevier, 2016)
An experimental study was conducted to investigate laser ignition using a diode laser for elastomer-modified cast double-base (EMCDB) propellant in order to develop more liable and greener laser ignitors for direct initiation of the propellant. Samples of the propellant were ignited using a 974 nm near-infrared diode laser. Laser beam parameters including laser power, beam width and pulse width were investigated to determine their effects on the ignition performance in terms of delay time, rise time and burn time of the propellant which was arranged in several different configurations. The results have shown that the smaller beam widths, longer pulse widths and higher laser powers resulted in shorter ignition delay times and overall burn times, however, there came a point at which increasing the amount of laser energy transferred to the material resulted in no significant reduction in either delay time or overall burn time. The propellant tested responded well to laser ignition, a discovery which supports continued research into the development of laser-based propellant ignitors.